2023
DOI: 10.1088/2631-6331/acbc64
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired composites: nature’s guidance for advanced materials future

Abstract: Biomimetics enables the use of nature as a source of inspiration for the elaboration of high-performance materials. In this scenario, the development of bioinspired composites emerges as a promising proposal, capable of generating technological innovation in numerous areas of engineering, considering the exceptional mechanical performance of materials of this kind. That said, this review article characterises the design principles and fundamental parameters for bioinspired composites design. In addition, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…As one promising direction of interdisciplinary fields, the study of bioinspired structural materials is booming. [1,2,12,13,[158][159][160][161][162][163] Various bioinspired materials, partially including bioinspired nacre-like materials, [69,76,77,83] bioinspired inverse nacre-like materials, [74,164,165] bioinspired multiple-arch elastic structural materials, [166,167] bioinspired polymeric honeycomb woods, [168,169] cuttlebone-inspired cellular materials, [170][171][172][173] as well as bioinspired Bouligand structural materials [151][152][153]174] have been fabricated. Many works showed that bioinspired materials with 3D bulk forms would occupy an increasingly prominent position in widespread structural applications.…”
Section: Discussionmentioning
confidence: 99%
“…As one promising direction of interdisciplinary fields, the study of bioinspired structural materials is booming. [1,2,12,13,[158][159][160][161][162][163] Various bioinspired materials, partially including bioinspired nacre-like materials, [69,76,77,83] bioinspired inverse nacre-like materials, [74,164,165] bioinspired multiple-arch elastic structural materials, [166,167] bioinspired polymeric honeycomb woods, [168,169] cuttlebone-inspired cellular materials, [170][171][172][173] as well as bioinspired Bouligand structural materials [151][152][153]174] have been fabricated. Many works showed that bioinspired materials with 3D bulk forms would occupy an increasingly prominent position in widespread structural applications.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of bio-inspired artificial laminates are nacre-like composites and hierarchical and biomimetic sandwich structures [33,34]. These materials are composed of multiple layers of different materials, arranged in a specific pattern to achieve high strength, toughness and adaptability [35]. One of the challenges in designing bio-inspired artificial materials for bone reconstruction involves creating a mathematical model that can characterize the complex structure of the biological system.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Currently, the clinically applied reconstruction substitutes are mainly bioinert materials such as titanium, and polyether ether ketone, which suffer from poor tissue integration and osteoconductivity. [ 2 ] Inspired by the precise component and unique structure of natural bone, bionic mineralized organic‐inorganic hybrid composites could combine the excellent properties of organic biomolecules and induced inorganic minerals [ 3 ] to provide congruent mechanical strength [ 4 ] and better osteogenesis. [ 1,5 ]…”
Section: Introductionmentioning
confidence: 99%